Aquatic Pollution Study Based on Analysis of Mollusk Diversity as a Bioindicator - Lohoo, Anneke V.; Manu, Gaspar; Mantiri, Rose O.S.E.; Kambey, Alex D. (Sam Ratulangi University, 2023)
This research aims to determine the condition of coastal water quality at Sam Ratulangi University's Marine Field Station by looking at the diversity of mollusks and the physical and chemical parameters of the waters as supporting parameters. The method used to determine the research location was the Quadratic Transect method, while to determine the sampling point the random sampling method was used, namely selecting sampling locations randomly based on areas with dominant activities. The mollusks taken are mollusks that are still alive and can be seen attached, both on the surface of the substrate and inside the substrate. Observations of the place and substrate where the individual attached/immersed themselves were carried out by measuring the water quality, where the temperature was 300C, salinity 28%0, and pH 8). The identification results obtained were 29 types. In the final step after the sample has been identified, all data obtained will be analyzed to obtain results from the research carried out. This research is expected to provide information about the condition of water pollution at Sam Ratulangi University's Marine Field Station in determining management policies and preserving the aquatic ecosystem. Keywords: Bioindicators, Molluscs, Diversity, Pollution. Abstrak Penelitian ini bertujuan untuk mengetahui kondisi kualitas perairan pesisir Marine Field Station Universitas Sam Ratulangi dengan melihat keanekaragaman moluska serta parameter fisika kimia perairan sebagai parameter pendukung. Metode yang digunakan dalam menentukan lokasi penelitian adalah metode Transek Kuadrat, sedangkan untuk menentukan titik pengambilan sampel digunakan metode random sampling, yaitu pemilihan lokasi pengambilan sampel secara acak berdasarkan kawasan dengan kegiatan yang dominan. Moluska yang diambil adalah Moluska dalam keadaan masih hidup yang terlihat menempel, baik di permukaan substrat maupun di dalam subtrat. Pengamatan tentang tempat maupun substrat dimana individu tersebut menempel/membenamkan diri dilakukan pengukuran kualitas air, di mana suhu 300C, salinitas 28%0 dan pH 8). Hasil indentifikasi diperoleh sebanyak 29 jenis. Langkah terakhir setelah sampel diidentifikasi, semua data yang diperoleh akan dianalisis untuk memperoleh hasil dari penelitian yang dilakukan. Penelitian ini diharapkan sebagai informasi tentang kondisi pencemaran perairan Marine Field Station Universitas Sam Ratulangi dalam penentuan kebijakan pengelolaan serta menjaga kelestarian ekosistem perairan. Kata kunci: Bioindikator, Moluska, Keanekaragaman, Pencemaran.